Decoding ageing: Handan Melike Dönertaş on microbiomes, AI and improving lifespan and healthspan (Communications Biology)
Investigating the complexities of ageing through computational biology, Handan Melike Dönertaş shares her journey from evolutionary genomics research at Middle East Technical University to leading her own lab at the Leibniz Institute on Ageing. Her team is developing and applying computational approaches aiming to advance our understanding of the microbiome and ageing.